Effect of water temperature on zoospore repeated emergence by waterborne Phytophthora cryptogea isolates - and K.B. KHARE*, D.O. OTAYE, S.L. VON BROEMBSEN (Indian Phytopathology, 2006)
Repeated emergence of zoospore (re-emergence) was assessed for Phytophthora cryptogea isolates, FDM51 and FWDM4. The effect of water temperature on this process was also assessed. Both vortex  encysted sporangial and cyst derived zoospores of these isolates exhibited repeated emergence. Repeated emergence (re-emergence) by SDZ cysts was higher (Pd"0.05) for P. cryptogea (FWDM4) at 20 and 25° C and optimum for P. cryptogea (FDM51) at 30° C. Phytophthora cryptogea (FWDM4) CDZ cysts had higher (Pd~0.05) re-emergence at 20 and 25° C than at 30° C, whereas, P. cryptogea (FDM51) had higher germination by reemergence at 30° C. There was a tendency for greater percent germination by re-emergence for CDZs than for SDZs for each P. cryptogea isolate considered in this study. Ability of this oomycetous plant pathogen to undergo repeated emergence could have far reaching implications in its management in irrigated agriculture.